Medicine stock Management at primary health care facilities in one South African province - Munedzimwe, Fadzai Eunice (Health Economics Unit, 2018)
As nations are encouraged to move towards achieving Universal Health coverage (UHC), access to essential medicines needs to be prioritized. In ensuring access to medicines, an important factor to be considered is the uninterrupted availability of essential medicines at the primary health care (PHC) level which is usually the first point of entry into the health system for patients. If South Africa is to move towards achieving UHC, the government must address the issue of unavailability of medicines due to frequent stock outs at the public health facilities. The increase in prevalence of HIV/AIDS and TB has resulted in an increase in the demand for medicines used in the management and treatment of these diseases. Surveys have revealed the extent of stock outs and shortages of medicines used in the management of HIV and TB in South Africa. It has also been predicted that the burden of disease in relation to these diseases is likely to increase in the coming years therefore, it is important for the South African government to address the issues of stock outs. Using a qualitative multiple case study approach, we explored the factors which may influence the management of medicine stock thus causing medicine stock outs at four PHC facilities in two of the districts in the study province. A conceptual framework on the factors influencing medicine stock outs at health facilities was developed from reviewing literature on the subject and this was used to guide data collection and analysis. Our findings revealed that the factors influencing the management of medicine stock leading to medicine stock outs include the lack of capacity in terms of human resources and physical resources at the PHC facilities. Insufficient supervision and support from the district level also had an influence as health workers at the facilities did not always follow the recommended procedures for medicine stock management. We also found that there were gaps in communication between the health workers at the facilities and stakeholders at other levels, particularly the pharmaceutical depot from which the facilities obtained their medicines. The inadequate information systems contributed to this gap in communication. Whilst many studies have focused on the factors that may influence the availability of medicine at higher levels, this study focused on what may influence it at the ground level, the PHC facility level. We anticipate that our findings will inform policy makers on how the availability of medicines at PHC facilities may be improved by focusing on improving the processes in medicine stock management at this level.